Basic teaching skill quality of teacher candidates in microteaching study subject of department of biology education, Pasir Pengaraian University - Afifah, Nurul (University of Muhammadiyah Malang, 2017)
This research purposed on knowing basic teaching skill quality of teacher candidates in study subject Microteaching of Department of Biology Education, Pasir Pengaraian University, academic year 2016/2016. This research is qualitative research. This research has been done in February to June 2015. The subject of this research is all of the 6th semester students who are taking the Microteaching Study Subject. The instruments of this research including syllabus, teaching plans, and questionnaire. The technique of collecting data in this research is from the researchâs informant, that is 1) The lecturer of Department of Biology Education, 2) The faculty lecturer (from Department of English Education, Mathematics Education, Physics Education, and Sport Education), and 3) The university lecturer (from other faculty in Pasir Pengaraian University). The technique which is use is data analysis technique according to Miles & Huberman that is data reduction, data presentation, and taking conclusion. The research results explain that the basic teaching skill quality of teacher candidates in Microteaching of Department of Biology Education, Pasir Pengaraian University with ratings of 3.13 or includes good criteria.